Protection Loop Error Measurement Based on Factor Analysis and Statistics Technology - Yawen YI; Chuanbin JIANG; Shiyu GONG; Xiaoyuan QIN; Jingpu ZHAO; Zhenxing LI (Zhongguo dianli)
In order to improve the reliability of the protection measurement circuit and ensure the safe operation of the power system, which requires the measurement error of the protection device to be solved in time. An error evaluation method based on factor analysis and statistical techniques is constructed for the protection measurement circuit in this paper. Based on the principle that there is strong linear correlation between the three phase data, the three-phase current obtained by the protection measurement circuit is analyzed and the error starting criterion is established. Based on the results of factor analysis, three classical statistics and control threshold in statistical techniques are used to locate the error source, and the evaluation accuracy of error less than 5% is achieved. The effectiveness and accuracy of this method are proved by simulation results.